Molecular Expressions : Scanning Electron Microscope (SEM) in Gills of Cyprinus carpio Infected Myxobolus sp. - Maftuch Maftuch; Bramantiyo Satriyo Wicaksosno; Febi Nadhila Nurin; Andhang Sebastian (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight Research:It has been found that many fish died with wounds from farmers in Blitar, Indonesia.The mucosal smear test from mucosal gills of C. carpio infected with Myxobolus.In the blood smear test of C. carpio, there was no myxobolus found in the blood.In gill organ testing using SEM that Myxobolus is found in gills (C. carpio).The shape of Myxobolus resembles an imperfect ball with a hollow in the middle. AbstractThe biggest problem that is often considered to be an obstacle to Common carp culture is the emergence of disease attacks. One type of disease that often attacks the seeds of Cyprinus carpio is Myxobolus (a systemic parasite that can cause harm to fish farming). The aim of this study was to determine the molecular expression through the smear test on C. carpio gills, to determine the image of the gill organs of C. carpio using the SEM test, and to determine the description of the spores of Myxobolus sp. Data were analyzed using descriptive methods. Descriptive method used was comparative descriptive comparing molecular expression in the test of gill mucosal smear of fish using a light microscope and gill organ testing using Scanning Electron Microscope (SEM) on C. carpio infected by Myxobolus sp. In this study, the results showed that in C. carpio infected with true Myxobolus found the presence of Myxobolus in the mucosal smear test and SEM test on gill tissue, but not found in the blood smear test.